การพัฒนาทักษะการสอนสำหรับครูภาษาไทยโดยใช้วิธีการสแกฟโฟล์ดิง กรณีศึกษา : โรงเรียนวัดโบราณสถิตย์ - แก้วสีขาว, วราภรณ์; ปิลันธนานนท์, นาตยา (Al-HIKMAH Journal, 2018)
Thai language is the vital instrument for communication so it is important for the Thai teachers to know about Thai principles and the variety of teaching approaches. In addition, this can support the students in developing the language skills as well as applying the knowledge in their daily lives. The purposes of the research were to develop the instructional skills packages for Thai language teachers and to study the effectiveness of using scaffolding approach in developing Thai language teachers’ instructional skills. The research populations were five Thai language teachers who encountered problems and obstacles with the instructions and also required to develop their instructional skills at Watboransathit School, The Narathiwat Primary Educational Service Area Office 2. This data was collected by the interview in the academic year of 2013. The research results were : 1) all five teachers encountered problems related to creative writing, summarizing main ideas, and composition writing 2) the scaffolding packages were used to practice those three instructional skills, and 3) the results from using skills practice packages revealed that (1) all teachers’ skills were developed at level two from three scoring rubrics and (2) they agreed that the skills practice packages were appropriate at the highest level, and they can further apply using the packages with the students.